Electronic commerce agent communication - Deepak S. Iyer (2008)
Electronic Commerce (E-commerce) has proven to be the most promising outcome of the explosive growth of the Internet. The design of software agents that facilitate E-commerce activities will drastically change the way business activities are held on the Internet. This project is an effort to design a large scale, distributed, agent-based electronic commerce system. This report first introduces the various agents that integrate to form our E-commerce system. The complete architecture of the system is explained along with detailed components of the different agents.